2023
DOI: 10.1128/spectrum.04472-22
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Novel B-Cell Epitopes of Capsid Protein VP2 in Senecavirus A

Abstract: The clinical symptoms and lesions caused by SVA are indistinguishable from those of other vesicular diseases in pigs. SVA has been associated with recent outbreaks of vesicular disease and epidemic transient neonatal losses in several swine-producing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Furthermore, the C-terminal region of VP2 ( 271 GLRNRFTTGTDEEQ 284 ) was identified as a diagnostic target for testing SVA antibodies in pigs (Ma et al, 2022). In the present study, the minimal epitope 266 SPYFNGL 272 of the C-terminus of VP2 was identified accurately by the mAb 2C7, and two amino acids (Gly 271 and Leu 272 ) were found overlapping with previous study conducted by Ma et al Recently, the epitope 267 PYFNGLRNRFTTGT 280 was predicted and identified by bioinformatics-based computational prediction and the Pepscan approach (Ru et al, 2023). However, we found that residue Ser 266 is important for maintaining the binding of 266 SPYFNGL 272 to mAb 2C7.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, the C-terminal region of VP2 ( 271 GLRNRFTTGTDEEQ 284 ) was identified as a diagnostic target for testing SVA antibodies in pigs (Ma et al, 2022). In the present study, the minimal epitope 266 SPYFNGL 272 of the C-terminus of VP2 was identified accurately by the mAb 2C7, and two amino acids (Gly 271 and Leu 272 ) were found overlapping with previous study conducted by Ma et al Recently, the epitope 267 PYFNGLRNRFTTGT 280 was predicted and identified by bioinformatics-based computational prediction and the Pepscan approach (Ru et al, 2023). However, we found that residue Ser 266 is important for maintaining the binding of 266 SPYFNGL 272 to mAb 2C7.…”
Section: Discussionsupporting
confidence: 79%
“…To date, several antigenic epitopes of SVA VP2 have been identified through bioinformatics prediction and synthetic polypeptide therapy using mAbs or porcine serum (Fan et al, 2020 ; Ru et al, 2023 ; Zhang et al, 2023 ). The 141 LDVRPDGKAKSLEELNEEQW 160 region is a dominant epitope region with relatively abundant epitopes in the VP2 protein (Fan et al, 2020 ; Wen et al, 2022 ; Ru et al, 2023 ; Zhang et al, 2023 ). In addition, Wen et al obtained five neutralizing mAbs by immunizing mice with ultra-purified SVA, and the linear epitope 153 QELNEE 158 recognized them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation